Strategi Pengembangan Agroindustri Minyak Sumbawa di Desa Kelungkung Kecamatan Batulanteh Menggunakan Analisis SWOT (International Forum of Researchers and Lecturers, 2023)
Sumbawa Besar Regency is one of the regencies in the West Nusa Tenggara region which has very abundant forestry resources. The forest is used as a business engaged in the extraction of forest products which is processed into various kinds such as Sumbawa oil which is produced in Kelungkung Village, Batulanteh District. The raw materials for making Sumbawa oil are obtained directly from the mountains and forests in the region which are efficacious as traditional medicines. The purpose of this study was to obtain a strategy and determine strategic priorities in the development of the Sumbawa oil agro-industry in Kelungkung Village, Batulanteh District. The stages of this research started with a field study by interviewing Sumbawa oil agro-industry players in Kelungkung Village, Batulanteh District. The analytical method used is SWOT analysis (Strengths, Weaknesses, Opportunities, Threats) and the QSPM matrix to obtain strategic priorities. Based on the results of the study, it was found that the position of the Sumbawa oil agro-industry was in quadrant I, namely supporting an aggressive strategy. Furthermore, based on the research results obtained by the QSPM matrix, 9 alternative strategies were obtained, and the prioritized strategy was to maintain and improve product quality according to tradition as a natural medicine that was of interest to consumers.